Entering the public sphere: the citizenship practices of US immigrants - Brettell, Caroline B. (Border Crossing, 2016)
This paper originally delivered as a keynote speech at the Turkish Migration Conference 2015 in Prague, Czech Republic on June 25, 2015. It focuses on civic engagementi political participation and citizenship practices of Asian Indians in Dallas Fort Worth Metropolitan area drawing on qualitative field research material. Community participation is a process. Embedded in this observation is an understanding that as the individual branches out, he or she is becoming involved with associations with great civic and/or political presence, moving from one community of practice to another, and from a peripheral position to one of greater participation to invoke the ideas of Lave and Wenger. But equally, these activities illustrate how new immigrants construct their own sense of belonging as they engage with and interpret what it means to be an American and what kind of an American they want to be.